Enhanced spectral sensitivity of fibre long period gratings to refractive index of aqueous solutions utilising copper patterned coatings - Kalli, Kyriacos; Allsop, Thomas P.; Dobb, Helen L. (My University, 2006)
A set of long period grating devices have been fabricated in photosensitive single mode fibre coated with a series of copper rings (period of 380μm, 50% duty cycle and length of 4cm). The long period gratings were inscribed with a uniform UV-laser exposure across the entire length of the copper ring patterned coating. The devices ranged in copper thickness from 0.5μm to 1.5μm. In addition, a control long period grating was fabricated in the same type of fibre with the same period for comparison. The refractive index and temperature spectral sensitivity of these devices were investigated and it was found that the index and temperature sensitivity is a function of the thickness of the copper rings, as supported by theoretical modelling. Furthermore, the index sensitivity of these devices in the 1.333 index region is greater than the control long period grating. The patterned 0.5μm coated long period grating gave a sensitivity of Δλ/Δn = -74 nm leading to a resolution of 1.4×10-3 compared to the control which had a sensitivity of Δλ/Δn = -32 nm with a resolution of 3.2×10-3 in the index region of 1.320 to 1.380 (aqueous solution regime). This demonstrates a two fold increase in the sensitivity. This novel fibre long period grating device shows potential for increasing the resolution of measurements of the index of aqueous solutions.
Keywords: Coatings; Copper; Diffraction gratings; Refractive index; Optical fibers